Dihydromyricetin Alleviates High Glucose-Induced Oxidative Stress and Apoptosis in Human Retinal Pigment Epithelial Cells by Downregulating miR-34a Expression - Li, Wenjun (Diabetes Metab Syndr Obes, 2021)
BACKGROUND: Diabetic retinopathy (DR) is one of the most common microvascular complications of diabetes mellitus, which leads to neuronal and vascular dysfunction in the retina with a final outcome of complete loss of vision. The aim of the present study was to investigate the effects of dihydromyricetin (DHM), a natural flavanol compound, on diabetic retinopathy (DR) and identify its potential mechanisms. METHODS: Retinal pigment epithelial cell line (ARPE-19) treated with high glucose (HG) was used to simulate the DR model in vitro. After treatment with different concentrations of DHM, the cell viability, production of reactive oxygen species (ROS) and the levels of oxidative stress-related markers in the in vitro model were detected using corresponding kits. Cell apoptosis was determined using terminal-deoxynucleotidyl transferase mediated nick end labeling (TUNEL) staining, and the expression of apoptotic proteins was examined using Western blot analysis. Subsequently, microRNA (miR)-34a expression was measured by reverse transcription-quantitative PCR (RT-qPCR). The levels of oxidative stress and apoptosis were evaluated after miR-34a overexpression. RESULTS: Results indicated that DHM dose-dependently elevated the decreased cell viability induced by HG. Moreover, the content of ROS was significantly reduced in HG-stimulated ARPE-19 cells, accompanied by enhanced activities of superoxide dismutase (SOD) and catalase (CAT) antioxidases, as well as concentration of glutathione (GSH). Furthermore, remarkably decreased apoptosis of ARPE-19 cells induced by HG was observed following DHM intervention. Importantly, HG stimulation notably upregulated miR-34a expression, which was reversed by DHM treatment. Importantly, the inhibitory effects of DHM on HG-induced oxidative stress and apoptosis of ARPE-19 cells were restored following miR-34a overexpression. CONCLUSION: Taken together, this work demonstrated that DHM exerts protective effects on HG-induced oxidative stress and apoptotic damage in ARPE-19 cells via inhibition of miR-34a expression, providing a promising therapeutic agent for the treatment of DR.